Isolation of an atypical Leptospira strain assigned to the Sejroe serogroup from a water buffalo in Brazil. (August 2021) - Guedes, Israel Barbosa; de Souza, Gisele Oliveira; de Paula Castro, Juliana Fernandes; Cavalini, Matheus Burilli; Maia, Anderson Luiz Pinheiro; do Amaral, Raquel Rodrigues; Cortez, Adriana; Heinemann, Marcos Bryan
Highlights: A Leptospira strain was recovered from urine of a water buffalo. The isolate was assigned to the species L. borgpetersenii and the Sejroe serogroup. This was the first isolation of a strain other than the subgroup Wolffi in Brazil. The strain was detected in the reproductive tract of experimentally infected hamsters. Abstract: The isolation of leptospires from buffaloes worldwide is still limited to a few strains. Thus, the aim of this study was to describe the first Leptospira isolate from buffalo urine, assigned to the Sejroe serogroup, which does not belong to the Wolffi subgroup, traditionally isolated in Brazil. A total of 244 urine samples of water buffaloes ( Bubalus bubalis ) raised in the Brazilian Amazon were subjected to bacteriological culturing and polymerase chain reaction (PCR) for the detection of leptospires. The obtained isolate was characterized by serogrouping using polyclonal antibodies, partial DNA sequencing, Hardjo-Bovis-specific PCR, multiple-locus variable-number tandem repeat analysis (MLVA/VNTR) and experimental infection in hamsters. PCR was performed on the urine samples; 11/244 were positive (4.5 %) for Leptospira, and only one isolate was recovered (0.4 %). Regarding characterization, the isolate was assigned to the Sejroe serogroup with high titers (12, 800) for the Saxkoebing and Sejroe serovar antisera. The isolate was negative for Hardjo-Bovis-specific PCR, and the species Leptospira borgpetersenii was identified by DNA sequencing. The MLVA results showed that the VNTR profile of the isolate was 1−2-5, compatible with that of serovars Sejroe/Istrica. In the experimental infection in hamsters, the animals did not develop clinical signs, and no macroscopic lesions were observed on the organs at necropsy; however, the strain was detected in the kidneys, uterus, and testicles of the animals. The isolate described herein highlights infection by Sejroe strains that may be overlooked in buffaloes and that may be different from those normally isolated and used in serological studies.